2017
DOI: 10.1021/acs.iecr.7b01587
|View full text |Cite
|
Sign up to set email alerts
|

Development of Potassium- and Sodium-Promoted CaO Adsorbents for CO2 Capture at High Temperatures

Abstract: Development of highly efficient adsorbents for the high temperature CO2 capture process is crucial for large scale implementation of this technology. In this work, development of novel potassium- and sodium-promoted CaO adsorbents (K–Ca and Na–Ca) is discussed, and their CO2 capture performance at high temperatures is presented. A series of K–Ca and Na–Ca adsorbents with various K/Ca or Na/Ca molar ratios were developed and tested for CO2 capture at high temperatures ranging from 300 to 400 °C. The structural,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 43 publications
4
48
0
Order By: Relevance
“…Al 2 O 3 or MgO) 7,[11][12][13][14][15][16][17] or the addition of alkali metal salts. [18][19][20][21][22][23] Currently, there is very limited understanding of the effect of the addition of alkali metal salts on the CO 2 capture performance of CaO; indeed, several works have reported conflicting results. [18][19][20][21] For example, it has been reported that the addition of alkali metal chlorides and hydroxides (with the exception of Li-based salts) strongly increases the CO 2 uptake capacity of CaO, although no cyclic stability data was reported.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Al 2 O 3 or MgO) 7,[11][12][13][14][15][16][17] or the addition of alkali metal salts. [18][19][20][21][22][23] Currently, there is very limited understanding of the effect of the addition of alkali metal salts on the CO 2 capture performance of CaO; indeed, several works have reported conflicting results. [18][19][20][21] For example, it has been reported that the addition of alkali metal chlorides and hydroxides (with the exception of Li-based salts) strongly increases the CO 2 uptake capacity of CaO, although no cyclic stability data was reported.…”
mentioning
confidence: 99%
“…20 Upon the addition of Na 2 CO 3 , the double carbonate Na 2 Ca(CO 3 ) 2 can form under reaction conditions. 22,23 The formation of Na 2 Ca(CO 3 ) 2 has been linked to an increase in the kinetics of both the carbonation and calcination reactions and an increased cyclic stability of the sorbent when compared to pristine CaO. 22,23 Recent work has explored the effect of the addition of the double salt (Li-K) 2 CO 3 to CaO on its CO 2 uptake.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The cyclic CO 2 uptake performance of alkali metal-modified CaO varies strongly depending on the nature of the alkali metal (i. e., Li, Na, K, Rb and Cs), the precursors used for synthesis (e. g., Na 2 CO 3 vs. NaCl) and the content of alkali metal salt added. [11,70,88] However, a general trend of a decreased CO uptake with increasing alkali metal content seems to hold for most studies. For high contents of Na and K (i. e., several mol %), independent of the precursor used, various authors have shown that the CO 2 uptake performance is decreased, possibly due to enhanced sintering effects.…”
Section: Alkali Metal Salt-modified Cao-based Sorbentsmentioning
confidence: 99%
“…Calcium oxide‐based solid sorbents that undergo cyclic carbonation and calcination reactions during CO 2 capture and regeneration, viz. CaO+CO 2 ↔CaCO 3 with Δ R H 0 298K =±179 kJ mol −1 , have emerged as a cost‐efficient class of CO 2 sorbents [9–12] . On the process level, the use of CaO‐based CO 2 sorbents is referred to as calcium looping (CaL).…”
Section: Introductionmentioning
confidence: 99%